WSN sensor node placement approach based on multi-objective optimization - Abidin H.Z.; Din N.M.; Radzi N.A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Wireless Sensor Network (WSN) with maximum coverage, minimum energy consumption and guaranteed connectivity can be achieved through an optimum sensor node placement scheme. A sensor node placement algorithm that utilizes Multi-objective Territorial Predator Scent Marking Algorithm (MOTPSMA) is presented in this paper. The MOTPSMA deployed in this paper uses the minimum uncovered area and minimum energy consumption as the objective functions subject to full connectivity constraint. The performance of the WSN deployed with MOTPSMA is then compared with another algorithm known as Multi-objective Evolutionary Algorithm based on Fuzzy Dominance (MOEA/DFD) in terms of coverage ratio, connectivity and energy consumption. Simulation results show that the WSN deployed with the proposed sensor node placement algorithm provides a larger coverage ratio, full connectivity and lower energy consumption. © 2014 IEEE.